2010
DOI: 10.1016/j.jtrangeo.2009.09.007
|View full text |Cite
|
Sign up to set email alerts
|

A spatial analysis of multiple airport cities

Abstract: This paper presents a detailed empirical description of airport connectivities in four major multiple airport cities (London, New York, Los Angeles, and San Francisco). Our analysis draws on data derived from a previously largely untapped information source, i.e. the socalled 'Marketing Information Data Transfer' (MIDT). This dataset contains information on actually flown transnational routes, which allows for a thorough assessment of the chief connectivity characteristics of specific airports. Combined with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Some studies found no significance [17], but others showed a more complex relationship: the development of urbanization promoting the optimal allocation of energy resources and agglomeration effects to reduce greenhouse gas emissions [18]. Other research proves the existence of urbanization with the environmental Kuznets curve as an inverted U-shaped curve [14,19].…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Some studies found no significance [17], but others showed a more complex relationship: the development of urbanization promoting the optimal allocation of energy resources and agglomeration effects to reduce greenhouse gas emissions [18]. Other research proves the existence of urbanization with the environmental Kuznets curve as an inverted U-shaped curve [14,19].…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Airports are increasingly part of multi-airport systems (MAS) (de Neufville, 1995;Derudder et al, 2010), implying multiple gateways for accessing metropolitan areas. Recent research has shown that LCCs not only influence pricing and traffic patterns at the airports they serve, but also at the other airports in a MAS (Brueckner et al, 2013;Tierney and Kuby, 2008;Vowles, 2001).…”
Section: The Impact Of Network Structure and Market Competition On Thmentioning
confidence: 99%
“…Such information is important in assessing uncertainties and risks of future investments in airport infrastructure in the country. Attention should also be paid here to the specific concentration and dispersal mechanisms behind traffic development in multi-airport regions (De Neufville, 1995;Derudder et al, 2010), such as the multi-airport system in Catalonia (Barcelona, Girona, Reus, Lleida 15 ), in Galicia (Santiago de Compostela, Vigo, A Coruña), in the Basque Country (Bilbo, Donostia-San Sebastián, Vitoria-Gasteiz), in Valencia and Murcia (Valencia, Alicante, Murcia), and in Andalucía (Sevilla, Málaga, Jerez de la Frontera, Granada, Almería).…”
Section: Discussionmentioning
confidence: 99%